(1) Solution:- 4x+1 = 2x+7
=> 4x-2x = 7-1
=> x= 6/2
= 3
(2) Solution:- 5x-3 = 2x+3
=> 5x-2x = 3+3
=> x = 6/3
= 2
(3) Solution:- 3y+1 = 7y-1
=> 3y-7y= -1-1
=> – 4y = -2
=> y= 2/4
= ½
(4) Solution:- 7y-5 = y-1
=> 7y-y = -1 +5
=> y= 4/6
= 2/3
(5) Solution:- 17-2z = 3z+2
=> -2z-3z = 2-17
=> – 5z = -15
=> z = 15/5
= 3
(6) Solution:- 13z-5 = 3-2z
=> 13z +2z = 3+5
=> z =8/15
(7) Solution:- x/4 = 1/3
=> x= 4/3
(8) Solution:- x/2+1= 3
=> x/2 = 3-1
=> x= 4
(9) Solution:- x/3+5 = x/2+7
=> x/3 – x/2 = 7-5
=> 2x-3x/6 = 2
=> -x= 12
=> x= -12
(10) Solution:- y/2 – y/3 = y/5 – 1/6
=> y/2 – y/3- y/5 = -1/6
=> 15y-10y-6y/30 = -1/6
=> -y/30 = -1/6
=> y = 30/6
=> y = 5
(11) Solution:- y/5- 2/7 = 5y/7 – 4/5
=> y/5 – 5y/7 = -4/5+27
=> 7y-25y/35 = 10-28/35
=> -18y/35 = -18/35
=> y= 18/18
=1
(12) Solution:- 2x-1/3 = 5
=> 2x-1 = 15
=> 2x= 15+1
=> x= 16/2
= 8
(13) Solution:- 5x/7 + 4/5 = x/5+ 2/7
=> 5x/7 – x/5 = 2/7-4/5
=> 25x-7x/35 = 10-28/35
=> 18x/35= -18/35
Therefore, x= -18/18
= -1
(14) Solution:- y-2/4 +2y-1/3 = y- 1/3
=> y-2/4 + 1/3 = y – 2y-1/3
=> 3(y-2) +4= 12y-4 (2y-1) [Both side x by 12]
=> 3y-6 + 4= 12y – 8y +4
=> 3y-12y+8y= 4+6-4
=> -y= 6
=> y= -6
(15) Solution:- 3y+1/5 = 3y-7/3
=> 15y-35 = 9y +3
=> 15y-9y= 3+35
=> 6y= 38
=> y= 38/6
= 19/3
(16) Solution:- x +1/2 – x-2/3 – x-3/5 = 2
=> 15x +15 – 10x +20 – 6x +18/30 = 2
=> -x +53/30 = 2
=> -x +53 = 60
=> -x = 60- 53
=> x= -7
(17) Solution:- 2(x+3) = 10
=>2x +6=10
=> x= 4/2
= 2
(18) Solution:- 5(x-2) = (x-4)
=> 5x-10 = 3x-12
=> 5x-3x = -12+10
=> 2x= -2
=> x = -2/2
= -1
(19) Solution:- 7(3-2y) + 5(y-1) = 34
=> 21-14y+5y-5 = 34
=> -9y = 34-21+5
=> -y= 18/9
=> y= -2
(20) Solution:- (z-1) (z+2) = (z+4) (z-2)
=> z2+2- z-2= z2-2z-2z+4z-8
=> z2+z-2= z2+2z-8
=> z2+z-z2= -8+2
=> -z= 6
Therefore, z= 6
No comments:
Post a Comment